A GTP-dependent Phosphoenolpyruvate Carboxykinase from Crassostrea gigas Involved in Immune Recognition. (December 2017) - Lv, Zhao; Qiu, Limei; Wang, Weilin; Liu, Zhaoqun; Xue, Zhuang; Yu, Zichao; Song, Xiaorui; Chen, Hao; Wang, Lingling; Song, Linsheng
Abstract: Phosphoenolpyruvate carboxykinase (PEPCK) is well known as a key enzyme involved in the metabolic pathway of gluconeogenesis in organisms, but the information about its involvement in immune response is still very limited. In the present study, a novel PEPCK homolog named CgPEPCK was identified from oyster Crassostrea gigas . The deduced amino acid sequence of Cg PEPCK shared 52%–74% similarities with those from other known PEPCKs. There were one conserved guanosine triphosphate (GTP) binding site, one substrate binding site, one metal binding site and one active site in Cg PEPCK. The mRNA transcripts of CgPEPCK were constitutively expressed in all the tested tissues including hemolymph, mantle, gill, muscle, gonad and hepatopancreas. Cg PEPCK proteins were mainly distributed in adductor muscle, gonad, gill and mantle, and rarely detected in hepatopancreas by using immunohistochemical analysis. After the stimulations with lipopolysaccharide (LPS), peptidoglycan (PGN), Vibrio splendidus and V. anguillarum, CgPEPCK transcripts in hemocytes were significantly up-regulated and peaked at 6 h (LPS, 9.62-fold, p  < 0.01), 9 h (PGN, 4.25-fold, p  < 0.01), 12 h ( V. splendidus, 5.72-fold, p  < 0.01), 3 h ( V. anguillarum, 2.87-fold, p  < 0.01), respectively. The recombinant Cg PEPCK protein (r Cg PEPCK) exhibited Mn 2+ /Mg 2+ dependent GTP binding activity, and the activities to bind LPS and PGN, but not β-1, 3-glucan (GLU), lipoteichoic acid (LTA), mannan (MAN) nor polyinosinic-polycytidylic (Poly I: C). It could also bind Escherichia coli, Staphylococcus aureus, Micrococcus luteus and significantly inhibit their growth. All these results collectively suggested that Cg PEPCK could not only exert GTP binding activity involved in gluconeogenesis, but also mediate the bacteria recognition and clearance in immune response of oysters. Highlights: A phosphoenolpyruvate carboxykinase was identified from Crassostrea gigas. In vitro, r Cg PEPCK could bind GTP in the presence of Mn 2+ /Mg 2+ . r Cg PEPCK exhibited binding activities to LPS, PGN and bacteria. Cg PEPCK mRNA transcripts in hemocytes were up-regulated after PAMPs or Vibrios stimulation. Cg PEPCK acted as a versatile molecule in gluconeogenesis, bacteria recognition and elimination.